Wet-spun flexible carbon nanotubes/polyaniline fibers for wearable thermoelectric energy harvesting. (March 2023) - Li, Hui; Liu, Yalong; Liu, Siqi; Li, Pengcheng; Zhang, Chun; He, Chaobin
Graphical abstract: Highlights: Flexible CNTs/PANI thermoelectric fibers were fabricated via wet-spinning approach. Properly modulating process parameters enhance their thermoelectric efficiency. Highest power factor of 176 μW m −1 K −2 was achieved for 84 wt% CNTs/PANI fiber. Continuous integrated p-n fiber was woven into wearable thermoelectric generator. Abstract: Flexible conducting polymer (CP) fiber-based thermoelectric generator (TEG) has gained significant interest for wearable electronics. Most of them however exhibit power factor much lower than 100 μW m −1 K −2, and few polyaniline (PANI) based fibers were studied despite PANI composites are environmental stable. Herein, novel high-performance flexible carbon nanotubes (CNTs)/PANI fibers were fabricated through facile wet-spinning approach, which leads to preferred orientation and facilitates carrier conduction along fiber. With properly modulating CNTs contents, coagulation bath duration, diameter of needle, and extrusion rate, microstructure and doping degree of CNTs/PANI fibers were fine-tuned, leading to a maximum power factor of 176 μW m −1 K −2 for 84 wt% CNTs/PANI fiber using needle with diameter of 23 G after ethanol bath for 1 min, which is the highest value among PANI based fibers and superior to most of the reported CP based fibers. Furthermore, TEG device was fabricated for promising wearable TE energy harvesting.